PENGEMBANGAN LKS PROJECT BASED LEARNING BERMUATAN SIKAP SPIRITUAL SOSIAL DENGAN PENILAIAN OTENTIK - Yeni Idayanti; Undang Rosidin; Eko Suyanto (Jurnal Pembelajaran Fisika, 2015)
This research aimed to develop project based learning student worksheet consisting social spiritual attitudes with authentic assessment which is attractive, easy, useful, and effective. This research used eight procedures, they were: pre- research and gathering the data, planning, developing the beginning product, testing the beginning product, revising product, testing the main field, revising the operational product, and testing the operational field. The final results showed that students cognitive and psychomotor aspect reached the mean score of 3.2 which means the students had good achievement in learning, the affective aspect including spiritual attitudes reached the mean score of 3.7 which means the students profile was very good categorize, and the social aspect reached the mean score of 3.4 which means the students had well categorize.Penelitian ini bertujuan untuk mengembangkan lembar kerja siswa project based learning bermuatan sikap spiritual sosial dengan penilaian otentik yang menarik, mudah, bermanfaat dan efektif. Penelitian ini menggunakan delapan prosedur, yaitu: penelitian dan pengumpulan data, perencanaan, pengembangan produk awal, uji coba produk awal, revisi produk utama, uji lapangan utama, revisi produk operasional dan uji lapangan operasional. Hasil akhir menunjukkan bahwa: aspek kognitif dan psikomotor siswa mencapai skor rata-rata sebesar 3,2 yang berarti siswa tuntas dalam belajar, aspek afektif yang meliputi sikap spiritual mencapai skor rata-rata 3,7 yang berarti profil diri dari siswa dalam kategori sangat baik, dan sikap sosial mencapai skor 3,4 yang berarti dalam kategori baik.Kata kunci: lembar kerja siswa, project based learning, sikap spiritual sosial.